The use of Dose Management Systems in Europe: Results of an ESR EuroSafe Imaging Questionnaire - Reinhard Loose; Eliseo Vaño; Josefin Ammon; Jonas Andersson; Hugues Brat; Boris Brkljacic; Katrina Caikovska; Riccardo Corridori; John Damilakis; Timo De Bondt; Guy Frija; Claudio Granata; et al. (Insights into Imaging, 2024)
Abstract Dose management systems (DMS) are an essential tool for quality assurance and optimising patient radiation exposure. For radiologists and medical physicists, they are important for managing many radiation protection tasks. In addition, they help fulfil the requirements of Directive 2013/59/EURATOM regarding the electronic transmission of dosimetric data and the detection of unintended patient exposures. The EuroSafe Imaging Clinical Dosimetry and Dose Management Working Group launched a questionnaire on the use of DMS in European member states and analysed the results in terms of modalities, frequency of radiological procedures, involvement of medical physics experts (MPEs), legal requirements, and local issues (support by information technology (IT), modality interfaces, protocol mapping, clinical workflow, and associated costs). Critical relevance statement Despite the great advantages of dose management systems for optimising radiation protection, distribution remains insufficient. This questionnaire shows that reasons include: a lack of DICOM interfaces, insufficient harmonisation of procedure names, lack of medical physicist and IT support, and costs. Key Points Quantitative radiation dose information is essential for justification and optimisation in medical imaging. Guidelines are required to ensure radiation dose management systems quality and for acceptance testing. Verifying dose data management is crucial before dose management systems clinical implementation. Medical physics experts are professionals who have important responsibilities for the proper management of dose monitoring. Graphical Abstract